CONSTRUCTING IDENTITY AND PERSUASION THROUGH LANGUAGE: A STUDY OF CAMPAIGN SLOGANS IN MALANG - Nadzierul Mujtaba; Eni Sugiharyanti; Ika Nurhayani (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
The 2024 Indonesian legislative election marked a significant phase in the evolution of political communication, especially at the local level, where candidates have limited access to mass media platforms. In urban areas such as Malang, East Java, Indonesia, where the population includes a large number of first-time voters, campaign strategies shifted toward outdoor media, like billboards. Though brief, these visual texts carry persuasive and symbolic linguistic elements. Language becomes a key instrument through which candidates seek to construct identity, establish cultural proximity, and influence voter behavior. Analyzing these linguistic choices is crucial to understanding how political messages are shaped by and respond to local social contexts. This study aims to investigate how language is used to construct identity and persuasion in the campaign slogans of local legislative candidates in Lowokwaru District, Malang City. The study explores how linguistic elements reflect strategies of self-representation and persuasion, as well as how these slogans accommodate the sociocultural values of their target audience. This research focuses on understanding the textual structure and communicative functions of these slogans. Using a qualitative descriptive approach, this study applies Halliday’s Systemic Functional Linguistics (SFL) framework to examine twenty-four campaign slogans displayed in public spaces near three major universities in Malang. Each slogan is analyzed through the three metafunctions: ideational, interpersonal, and textual. Additionally, these slogans are interpreted based on the situational context, particularly field, tenor, and mode. The data were collected through visual documentation and were analyzed using clause-based linguistic analysis. The findings reveal that most slogans employ relational and material processes, imperative moods, and high-modality expressions to deliver direct and emotionally-charged appeals. Candidates strategically use inclusive, religious, and culturally-embedded phrases to build rapport with voters. Although these slogans are textually short, they are also thematically cohesive and structured to enhance memorability. The use of local and Islamic expressions underscores a deliberate alignment with the sociocultural identity of young, religious voters. This study contributes to political discourse analysis by demonstrating how campaign slogans function not only as persuasive tools but also as social semiotic instruments for negotiating identity, and ideology. It offers insights into how language use in political campaigns reflects broader sociopolitical dynamics, especially in regions where localized values and youth demographics play a central role in electoral engagement.